In situ Generated Ru(0)-HRO@Na-β From Hydrous Ruthenium Oxide (HRO)/Na-β: An Energy-Efficient Catalyst for Selective Hydrogenation of Sugars - Gundekari, Sreedhar; Desai, Heena; Ravi, Krishnan; Mitra, Joyee; Srinivasan, Kannan (Frontiers in Chemistry, 2020)
A green process for the hydrogenation of sugars to sugar alcohols was designed in aqueous medium using hydrous ruthenium oxide (HRO) as a pre-catalyst supported on Na-β zeolite. Under optimized reaction conditions, sugars such as xylose, glucose, and mannose converted completely to the corresponding sugar alcohols xylitol, sorbitol, and mannitol with 100% selectivity. The pre-catalyst (HRO) is converted in situ to active Ru(0) species during the reaction under H2, which is responsible for the hydrogenation. The catalyst was recyclable up to five cycles with no loss in activity. The reduction of HRO to the active Ru(0) species is dependent on the reaction temperature and H2 pressure. Ru(0) formation increased and consequently an increased hydrogenation of sugars was observed with an increase in reaction temperature and hydrogen pressure. Further, in situ generation of Ru(0) from HRO was assessed in different solvents such as water, methanol, and tetrahydrofuran; aqueous medium was found to be the most efficient in reducing HRO. This work further demonstrates the use of supported HRO as an efficient pre-catalyst for biomass-based hydrogenation reactions.